Jul 2, 2018 - In this note we give a complete proof of a theorem of Dedekind. Keywords ... proof is a somewhat detailed version of the one given in Basic Algebra by ... (This is the fundamental theorem of finitely generated Abelian groups).
Open Journal of Discrete Mathematics, 2018, 8, 73-78 http://www.scirp.org/journal/ojdm ISSN Online: 2161-7643 ISSN Print: 2161-7635
On Tate’s Proof of a Theorem of Dedekind Shiv Gupta Department of Mathematics, West Chester University, West Chester, PA, USA
How to cite this paper: Gupta, S. (2018) On Tate’s Proof of a Theorem of Dedekind. Open Journal of Discrete Mathematics, 8, 73-78. https://doi.org/10.4236/ojdm.2018.83007
Abstract
Received: March 13, 2018 Accepted: June 29, 2018 Published: July 2, 2018
Galois Group of a Polynomial
Copyright © 2018 by author and Scientific Research Publishing Inc. This work is licensed under the Creative Commons Attribution International License (CC BY 4.0). http://creativecommons.org/licenses/by/4.0/ Open Access
In this note we give a complete proof of a theorem of Dedekind.
Keywords
1. Introduction In this note we give a complete proof of the following theorem of Dedekind. Our proof is a somewhat detailed version of the one given in Basic Algebra by Jacobson, Volume I, [1] and we shall keep the notations used in that proof.
Theorem 1 Let f ( x ) ∈ [ x ] be square-free monic polynomial of degree n
and p be a prime such that p does not divide the discriminant of f ( x ) . Let G ⊂ Sn be the Galois group of f ( x ) over the field of rational numbers. Suppose that f p= f= f ( mod p ) ∈ p [ x ] factors as: f p= f=
r
∏ fi i =1
where fi are distinct monic irreducible polynomials in p [ x ] , degree fi = di , 1 ≤ i ≤ r , and d1 + d 2 + + d r = n. Then there exists an automorphism σ ∈ G which when considered as a permutation on the zeros of f ( x ) is a product of disjoint cycles of lengths d1 , d 2 , , d r .
( )
2. Preliminary Results We shall assume that the reader is familiar with the following well-known results.
1) Let be a field and f ( x ) ∈ [ x ] be a polynomial of degree n ≥ 2 . Then any two splitting fields of f ( x ) are isomorphic. 2) A finitely generated Abelian group is direct sum of (finitely many) cyclic
DOI: 10.4236/ojdm.2018.83007 Jul. 2, 2018
73
Open Journal of Discrete Mathematics
S. Gupta
groups. (This is the fundamental theorem of finitely generated Abelian groups). 3) A system of n homogeneous equation in m > n variables has a non-trivial solutions. 4) Let / be an algebraic extension. Then any subring of containing
is a subfield of . Proof: Let K be a ring such that ⊂ K ⊂ . Let
α ∈ K − . As α is algebraic over , (α ) = [α ] . So α −1 ∈ (α ) ⊂ K . 5) (Dedekind’s Independence Theorem). Distinct characters of a monoid (a set with associative binary operation with an identity element) into a field are linearly independent. That is if χ1 , χ 2 , , χ n are distinct characters of a monoid into a field , then the only elements ai ∈ , 1 ≤ i ≤ n , such that a1 χ1 ( h ) + a2 χ 2 ( h ) + + an χ n ( h ) = 0
for all h ∈ H are ai = 0 , 1 ≤ i ≤ n . 6) Let p be a prime and GF ( p m ) be a finite field with p m elements. Then the group Aut GF p m = σ is cyclic of order m and the generating
( ( ))
automorphism σ maps α ∈ GF ( p m ) to α p . 7) If R is a commutative ring with identity and M is a maximal ideal of R then
R/M is a field. 8) Let σ ,η ∈ Sn . Then σ and η −1ση have same cyclic structure. Let f ( x ) ∈ [ x ] be a polynomial of degree n ≥ 1 , and p a prime number. Then f p ( x ) ∈ p [ x ] will denote the polynomial obtained by reducing the coefficients of f ( x ) modulo p. Theorem 2 Let f ( x ) ∈ [ x ] be a monic polynomial of degree n ≥ 1 and p be a prime number which does not divide the discriminant of f ( x ) . Let be a splitting field of f ( x ) over . Let p be a splitting field of f p ( x ) over p = / ( p ) . Let f ( x) =
( x − r1 )( x − r2 ) ( x − rn ) ,
ri ∈ ⊂ ,1 ≤ i ≤ n
R = {r1 , r2 , , rn } , = Rp
{r , r , , r } ⊂ 1
2
n
p
where ri , 1 ≤ i ≤ n are the roots of f p ( x ) ∈ p [ x ] and
(
= = ( r1 , r2 , , rn ) , p p r1 , r2 , , rn
)
Let D = [ r1 , r2 , , rn ] be the subring generated by the roots of r1 , r2 , , rn of f ( x ) in . Then • 1) There exists a homomorphism ψ of D onto p . • 2) Any such homomorphism ψ gives a bijection of the set R of the roots of f ( x ) in onto the set R p of the roots of the f p ( x ) in p . • 3) If ψ and ψ ′ are two such homomorphisms then there exist σ ∈ Aut ( / ) = Gal ( f ( x ) ) , such that ψ =′ ψ ⋅ σ . (Note that the restriction of σ to D is an automorphism of D). Proof 1) One has that:
= = ( r1 , r2 , , rn ) [ r1 , r2 , , rn ] DOI: 10.4236/ojdm.2018.83007
74
Open Journal of Discrete Mathematics
S. Gupta
We claim that D = [ r1 , r2 , , rn ] is a finitely generated (additive) Abelian
group. Since each ri is a root of the monic polynomial f ( x ) ∈ [ x ] of degree n any positive power of ri ,1 ≤ i ≤ n can be expressed as an integral linear combination of 1, ri , ri 2 , ri n−1 . It follows that D=
∑
r1e1 r2e2 rnen .
0≤ei ≤n −1
Therefore D is a finitely generated (additive) Abelian group generated by at most nn elements. By the Fundamental Theorem for Finitely Generated Abelian
Groups D is a direct sum of finitely many cyclic groups. Since D ⊂ , none of these cyclic groups is finite. So D is a direct sum of finitely many infinite cyclic groups. Let {u1 , u2 , , u N } be a set consisting of an independent generating system of D. We have D = u1 ⊕ u2 ⊕ ⊕ u N , We claim that
{u1 , u2 , , u N }
N ≤ nn .
is a basis of / . Obviously
{u1 , u2 , , u N }
is linearly independent over . Let D = ∑1≤i≤ Nui . Then D is a ring and ⊂ D ⊂ therefore D is a field. Since ri ∈ D for 1 ≤ i ≤ n , by (4) D = and {u1 , u2 , , u N } is a basis of E / . As
D = u1 ⊕ u2 ⊕ ⊕ u N ,
= pD ( pu1 ) ⊕ ( pu2 ) ⊕ ⊕ ( pu N )
is an ideal of D and
D pD=
{a u + a u 1 1
2 2
}
+ + aN u N : 0 ≤ ai ≤ p − 1 .
Therefore the D pD is finite of order p N . Let M be a maximal ideal of D containing pD. That is pD ⊂ M ⊂ D and D M is a finite field of characteristic p and so it has a subfield isomorphic to p = / p which we will identify as p in what follows. As
D M≈
D pD M pD
the order of D M is p m , 1 ≤ m ≤ N . Consider the canonical epimorphism
ν :D→D M whose kernel is M and p ⊂ M . Therefore ν ( ) = p . We note that as D = [ r1 , r2 , , rn ] we have for 1 ≤ i ≤ n
ν ( ri ) =ri + M =ri , ν ( D ) = p r1 , r2 , , rn As ν is an epimorphism we have
ν= M p r1 , r2 , , rn ( D ) D= is a splitting field of f p ( x ) over p . As both D M and p are splitting fields of f p ( x ) over p they are isomorphic. Let
φ : D M → p be such an isomorphism. Then ψ = φ ⋅ν is a homomorphism of D onto p . DOI: 10.4236/ojdm.2018.83007
75
Open Journal of Discrete Mathematics
S. Gupta
2) Let ψ : D → p be a homomorphism. So ψ (1) = 1 . As ⊂ D , and p has characteristic p, ψ ( p ) = 0 , so ψ ( = ) p ⊂ p . ψ can be extended to a homomorphism of the polynomial rings D [ x ] → p [ x ] . Under this mapping f ( x ) → f p ( x ) . As
f ( x) = ( x − r1 )( x − r2 ) ( x − rn )
ψ ( f ( x )) = f p ( x) = ( x −ψ ( r1 ) ) ( x −ψ ( r2 ) ) ( x −ψ ( rn ) ) ,
ψ ( ri ) ,1 ≤ i ≤ n are the roots of the f p ( x ) in p and therefore the restriction of ψ to R
{
ψ | R : {r1 , r2 , , rn } → r1 , r2 , , rn
}
is a bijection of the set R of roots of f ( x ) in to the set R p of the roots of f p ( x ) in p . 3) We have seen that given a homomorphism ψ : D → p , and σ ∈ Gal ( f ) = Aut ( / ) , ψ =′ ψ ⋅ σ is also a homomorphism from D to p . We note that the restriction of σ ∈ Aut ( / ) to D = [ r1 , r2 , , rn ] is also an automorphism of the ring D. Since [ : ] = N , the group Aut ( / ) has order N. Let
Aut ( / ) = {σ 1 , σ 2 , , σ N } So given a non-trivial homomorphism ψ : D → p , we get N distinct homomorphisms ψ j= ψ ⋅ σ j , 1 ≤ j ≤ N , from D to p . We claim that these are all the homomorphisms from D to p . Suppose that there is a homomorphism from D to p which is different from ψ j , 1 ≤ j ≤ N . Let us denote it by ψ N +1 . By Dedekind Independence Theorem the set {ψ 1 ,ψ 2 , ,ψ N ,ψ N +1} of N + 1 homomorphisms from D to p is linearly independent over the field p . Consider the following system of N homogeneous equations in N + 1 variables { x1 , x2 , , xN , xN +1} , N +1
∑ xiψ i ( u = j)
0, 1 ≤ j ≤ N .
i =1
Since there are more variables than the equations this system of equations has ai ∈ p , 1 ≤ i ≤ N + 1 . a non-trivial solution. Let this non-trivial solution be x= i So we have i= N +1
∑ aiψ i ( u = j)
0, 1 ≤ j ≤ N .
i =1
Let y ∈ D = u1 ⊕ u2 ⊕ ⊕ u N . So y = n1u1 + n2u2 + + nN u N , nk ∈ , 1 ≤ k ≤ N . Then for 1 ≤ i ≤ N + 1 we have
ψ i= uN ) ( y ) n1ψ i ( u1 ) + n2ψ i ( u2 ) + + nNψ i (=
j=N
∑ n jψ i ( u j ) j =1
n j + ( p ) . We shall show that where n= j i= N +1
∑ aiψ i ( y ) = 0, i =1
DOI: 10.4236/ojdm.2018.83007
76
Open Journal of Discrete Mathematics
S. Gupta
which will contradict the linear independence of {ψ 1 ,ψ 2 , ,ψ N ,ψ N +1} over
p .
=i N +1
∑ aiψ i ( y ) i =1
=
=i N +1
j=N
∑ ai ∑ n jψ i ( u j )
=i 1 =j 1
=
=i N +1
∑ ai ( n1ψ i ( u1 ) + n2ψ i ( u2 ) + + nNψ i ( uN ) ) i =1
= n1
i= N +1
i= N +1
i= N +1
∑ aiψ i ( u1 ) + n2 ∑ aiψ i ( u2 ) + + nN ∑ aiψ i ( uN )
=i 1 =i 1
=i 1
= 0.
3. Proof of the Main Theorem Since the field p has order p m , the group Aut ( p ) has order m and
π : p → p
where
π (a) = a p
for
a∈p ,
all
is
the
generating
automorphism of Aut ( p ) . So if ψ : D → p is any homomorphism then so
is π ⋅ψ . Since ψ and π ⋅ψ are two homomorphisms from D to p there
exist σ ∈ Aut ( / ) such that π ⋅ψ = ψ ⋅ σ or ψ −1 ⋅ π ⋅ψ = σ . This proves
{r1 , r2 , , rn }
that the action on σ on
is similar to the action of π on
{r , r ,, r } . Note: In the following diagram the mapping 1
2
n
σ →D D
is the restriction of σ ∈ Aut ( / ) to D and we are only concerned with the
{r1 , r2 , , rn }
effect of the mappings σ , ψ and π on
and
Clearly
{r , r , , r } . 1
2
n
σ → {r1 , r2 , , rn } {r1 , r2 , , rn }
{r , r ,, r } →{r , r ,, r } {r , r , , r } → {r , r , , r } 1
2
n
1
2
n
π
ψ
1
2
n
1
2
n
As ψ −1 ⋅ π ⋅ψ = σ and ψ ⋅ σ ⋅ψ −1 = π the effect of σ on similar to the effect of π on following:
{r1 , r2 , , rn }
is
{r , r ,, r } . This is further illustrated by the 1
2
n
()
rj ⇒ π ri = rj σ ( ri ) = −1
ψ σ ψ ri → ri → rj → rj
()
π ri = rj ⇒ σ ( ri ) = rj −1
ψ π ψ ri → ri → rj → rj
DOI: 10.4236/ojdm.2018.83007
77
Open Journal of Discrete Mathematics
S. Gupta
References [1]
DOI: 10.4236/ojdm.2018.83007
Jacobson, N. (2014) Basic Algebra. 2nd Edition, Dover Publications, Inc., Mineola, New York.
78
Open Journal of Discrete Mathematics